Operation and challenges of home-based medical practices in the US: findings from six aggregated case studies - Gregory J. Norman; Kristann Orton; Amy Wade; Andrea M. Morris; Jill C. Slaboda (BMC, 2018)
Abstract Background Home-based primary care (HBPC) is a multidisciplinary, ongoing care strategy that can provide cost-effective, in-home treatment to meet the needs of the approximately four million homebound, medically complex seniors in the U.S. Because there is no single model of HBPC that can be adopted across all types of health organizations and U.S. geographic regions, we conducted a six-site HBPC practice assessment to better understand different operation structures, common challenges, and approaches to delivering HBPC. Methods Six practices varying in size, care team composition and location agreed to participate. At each site we conducted unstructured interviews with key informants and directly observed practices and procedures in the field and back office. Results The aggregated case studies revealed important issues focused on team composition, patient characteristics, use of technology and urgent care delivery. Common challenges across the practices included provider retention and unmet community demand for home-based care services. Most practices, regardless of size, faced challenges around using electronic medical records (EMRs) and scheduling systems not designed for use in a mobile practice. Although many practices offered urgent care, practices varied in the methods used to provide care including the use of community paramedics and telehealth technology. Conclusions Learnings compiled from these observations can inform other HBPC practices as to potential best practices that can be implemented in an effort to improve efficiency and scalability of HBPC so that seniors with multiple chronic conditions can receive comprehensive primary care services in their homes.